Dopamine regulation of social choice in a monogamous rodent species - Aragona, Brandon J.; Wang, Zuoxin (Frontiers in Behavioral Neuroscience, 2009)
There is growing appreciation that social decision making in humans is strongly influenced by hedonic and emotional processing. The field of social neuroeconomics has shown that neural systems important for reward are associated with social choice and social preferences in humans. Here, we show that the neurobiology of social preferences in a monogamous rodent species, the prairie vole, is also regulated by neural systems involved in reward and emotional processing. Specifically, we describe how mesolimbic dopamine transmission differentially mediates the formation and maintenance of monogamous pair bonds in this species. Thus, reward processing exerts tremendous regulation over social choice behaviors that serve as the foundation of a rather complex social organization. We conclude that prairie voles are an excellent model system for the neuroscience of social choice and that complex social decision-making can be robustly explained by reward and hedonic processing.